Groups Analysis Of Spiders Species By Preferences For Tirana Habitat Area - Muca, Markela; Vrenozi, Blerina (European Scientific Journal, ESJ, 2016)
In this paper, we presented the cluster analysis of ground-dwelling spiders. The scientific material was collected from different areas of the Tirana district, using traps Pitt. Preferences per habitat have shown that areas of the Veterinary Research Institute and the mount of Dajti have a larger number of species that are abundant in various habitats. Also, depending on the areas, it can be classified into three major groups: The Vora hills, Tirana city, and the Dajti Mountain. The analysis is based on a sample which consists of 123 ground-dwelling spiders scattered mostly in seven areas. The results of the analysis have shown the spider distribution in at least one of the areas included in the study. In addition, it also shows the dominant species for each area. All analysis is performed using SPSS statistics 20.